Dynamics of Inclusion of Accession Countries into the European Monetary Union : Some Institutional Aspects - Vladimir Lavrač (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
The main topic of the paper is optimal dynamics, i.e., timing of entry of the accession countries in the ERM 2 and EMU. Some of the crucial questions addressed in the paper are as follows: a) Should accession countries aim at an early or a delayed entry into the EMU? b) What are economic and other arguments for an early or late inclusion? c) What are the institutional external constraints which may prevent an early inclusion of accession countries? Institutional rules of the phased process of monetary integration for the accession countries are not quite transparent and leave much room for discretion to the EU side. In such circumstances it is difficult for the accession countries to devise clear and consistent strategies with respect to the timing of entry in the ERM 2 as an interim institutional mechanism in the run-up to the EMU.
Keywords: E6; 330; EMU; ERM 2; monetary integration; institutional economics; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Institutioneller Wandel; EU-Staaten; Osteuropa